EXPERIENCE UTILIZING THE CANADIAN OCCUPATIONAL PERFORMANCE MEASURE (COPM) IN THE DEVELOPMENT OF INDIVIDUAL REHABILITATION PROGRAMS FOR MIDDLE-AGED INDIVIDUALS WITH CHRONIC CALCULOUS CHOLECYSTITIS AFTER CHOLECYSTECTOMY - Golod, N. R.; Zharova, I. O.; Nikanorov, O. K. (Rehabilitation and Recreation, 2025)
Objective is to describe the experience of using the Canadian Occupational Performance Measure (COPM) in the development of individual rehabilitation programs for middle-aged individuals after cholecystectomy; to determine the dynamics of the quality of life of middle-aged patients after cholecystectomy under the influence of the developed individual rehabilitation programs using COPM.Material. Middle-aged patients aged 45 to 59 years with chronic calculous cholecystitis (CCC) after cholecystectomy (n=40) who underwent laparoscopic cholecystectomy were included. Patients in the main group (n=20) received rehabilitation according to our concept using a biopsychosocial individual approach andCOPM, patients in the control group (n=20) received general recommendations on diet and exercise regimens.The mental and physical components of quality of life were assessed using the SF-12 questionnaire, in orderto ensure client-centeredness when setting short-term goals in the process of developing and implementingindividual rehabilitation programs aimed at occupational activity, the COPM was used. The article presents the results of assessing the quality of life at the acute stage of rehabilitation (initial examination), in the post-acute stage (one month after laparoscopic cholecystectomy (LCC)) and long-term stage (one year after LCC).Statistical methods: Shapiro-Wilk W-test, the mean (x )̅, standard deviation (S) and standard error of the mean (m) were calculated; Student’s t-test, differences were considered statistically significant at p<0.05.Results. The results of the SF-12 quality of life survey in individuals with CCC indicate a level of lifeslightly below the average in the physical and mental components. This indicates that chronic calculouscholecystitis negatively affected these two important factors of quality of life. Analyzing the dynamics of quality of life according to the SF-12 questionnaire one month after LCC, no statistically significant (p > 0.05) changes in quality of life were found in any of the groups. The results of the dynamics of quality of life according to the SF-12 questionnaire in individuals with CCC one year after LCC indicate a statistically significant (p<0.05) improvement in the control group compared to the previous examination.The results of the dynamics of the quality of life according to the SF-12 questionnaire in individuals with CCC one year after LCC indicate a statistically significant (p < 0.05) improvement in the representativesof the main group compared to the previous examination and compared to the control group one year later,which indicates a more positive dynamics in the quality of life in the physical and mental components. Conclusions. COPM allows taking into account the personal factors of patients when developingindividual rehabilitation programs aimed at restoring occupational activity in individuals aftercholecystectomy and ensuring client-centeredness of occupational therapy intervention. The use of COPMin individuals after cholecystectomy increases their motivation to continue rehabilitation in long-termstages, directs interdisciplinary work to all areas of quality of life. It has been established that the use of COPM in the concept of restoring the quality of life of individuals after cholecystectomy leads to animprovement in its mental and physical components.